Nursing cooperation of balloon compression and double bronchoscope method for a patient with massive hemorrhage occurring during bronchoscopy (双软镜联合球囊压迫成功救治支气管镜诊疗操作相关大出血1例护理配合) - MENG Lihua (孟丽华); WANG QIN (王琴); LI Shan (李杉); XIA Ying (夏莹) (中西医结合护理)
This paper summarized the key points in nursing cooperation of balloon compression and double bronchoscope method for a patient with massive hemorrhage occurring during bronchoscopy. Key issues of nursing included preoperative preparation, intraoperative cooperation such as body position placement and hemostasis by balloon compression, postoperative observation and double bronchoscope method. Multidisciplinary team-based interventions were carried to ensure optimal outcomes and patient safety during surgery. (总结1例支气管镜诊疗操作相关大出血的护理配合要点, 包括术前准备、术中配合(体位摆放、球囊压迫止血护理配合等)、术后观察、双软镜联合操作配合要点等, 通过多学科合作, 快速救治患者, 确保患者生命安全。)